Impacto de las aplicaciones multimedia y su importancia dentro del proceso de enseñanza aprendizaje en la asignatura de lengua y comunicación del octavo año de educación básica del Colegio Nacional Remigio Geo Gómez de la ciudad de Huaquillas , periodo lectivo 2012-2013. - Carrera Córdova, Germania Lorena (2013)
highlights two fundamental principles in current discussions on the status and role of teachers, the first of this is to argue that today, more than ever, educational reforms must reach schools and the classroom and therefore, the teacher is the key player in the process of educational transformation, the second principle, refers to the need to design comprehensive policies for teachers, exceeding partial approaches based on the way that it is possible to change the situation by modifying a one aspect of the problem.